2010
DOI: 10.1016/j.ydbio.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The hormonal pathway controlling cell death during metamorphosis in a hemimetabolous insect

Abstract: Metamorphosis in holometabolous insects is mainly based on the destruction of larval tissues. Intensive research in Drosophila melanogaster, a model of holometabolan metamorphosis, has shown that the steroid hormone 20-hydroxyecdysone (20E) signals cell death of larval tissues during metamorphosis. However, D. melanogaster shows a highly derived type of development and the mechanisms regulating apoptosis may not be representative in the insect class context. Unfortunately, no functional studies have been carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 40 publications
4
44
0
Order By: Relevance
“…S1 I-N). Recently, we have shown that a complex 20E-triggered hierarchy of nuclear receptors controls these metamorphic transformations in B. germanica (11,12). The same gene cascade, however, is also present during the previous nymphal-nymphal transitions (12), implying that stage-specific factors modify the responsiveness of target genes during the metamorphic transition.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…S1 I-N). Recently, we have shown that a complex 20E-triggered hierarchy of nuclear receptors controls these metamorphic transformations in B. germanica (11,12). The same gene cascade, however, is also present during the previous nymphal-nymphal transitions (12), implying that stage-specific factors modify the responsiveness of target genes during the metamorphic transition.…”
Section: Resultsmentioning
confidence: 95%
“…S1 A-H). During this transition, the prothoracic gland, which is responsible for the synthesis of ecdysteroids, degenerates, and the corpora allata cells switch from the proliferative phase to the adult-specific nonproliferative state (11) (Fig. S1 I-N).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, BgFTZ-F1 induces the degeneration of the prothoracic gland immediately after the imaginal molt, a critical event required for proper adult development in B. germanica 54. BgFTZ-F1 acts, therefore, as a critical adult-specific factor in the two main endocrine glands, the prothoracic gland where induces its degeneration, and the CA where promotes the synthesis of high levels of JH.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the reported data on this cascade of transcription factors refer to Drosophila melanogaster , the fruit fly, a holometabolous insect that shows many highly derived characters, which has been the most thoroughly studied species from the point of view of molecular endocrinology89. From this point of view, the most widely studied hemimetabolous model is the German cockroach Blattella germanica , and results indicate that the transcription factors involved in 20-hydroxyecdysone signalling are generally conserved, although the functions of some of them and the precise epistatic relationships between them may differ with respect to D. melanogaster 1011121314.…”
mentioning
confidence: 99%